2009
DOI: 10.1038/nature08088
|View full text |Cite
|
Sign up to set email alerts
|

Peierls distortion as a route to high thermoelectric performance in In4Se3-δ crystals

Abstract: Thermoelectric energy harvesting-the transformation of waste heat into useful electricity-is of great interest for energy sustainability. The main obstacle is the low thermoelectric efficiency of materials for converting heat to electricity, quantified by the thermoelectric figure of merit, ZT. The best available n-type materials for use in mid-temperature (500-900 K) thermoelectric generators have a relatively low ZT of 1 or less, and so there is much interest in finding avenues for increasing this figure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
451
3
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 521 publications
(489 citation statements)
references
References 18 publications
21
451
3
4
Order By: Relevance
“…Th is review covers the latest advancements in TE technology focusing on such nanostructural approaches, and in doing so aims to highlight the potential routes for improvement in the major TE material systems, including Bi-Te alloys, skutterudites, Ag-Pb-Sb-Te or 'LAST', half-Heusler alloys and some high-ZT oxides. Certainly, there are also other useful approaches for enhancing TE properties, such as band structure engineering by doping [17,20] and exploring new materials with complex crystalline structure [21,22], but such approaches are beyond the scope of the current review.…”
Section: Review Articlementioning
confidence: 99%
“…Th is review covers the latest advancements in TE technology focusing on such nanostructural approaches, and in doing so aims to highlight the potential routes for improvement in the major TE material systems, including Bi-Te alloys, skutterudites, Ag-Pb-Sb-Te or 'LAST', half-Heusler alloys and some high-ZT oxides. Certainly, there are also other useful approaches for enhancing TE properties, such as band structure engineering by doping [17,20] and exploring new materials with complex crystalline structure [21,22], but such approaches are beyond the scope of the current review.…”
Section: Review Articlementioning
confidence: 99%
“…Of note, these values are significantly lower than those measured in Bi 2 Te 3 -based alloys but similar to those achieved in α-As 2 Te 3 or in other chalcogenides. 2,10,[22][23][24][25][26][27] In the parallel direction, κ L approaches the lowest limit of the thermal conductivity (Figure 2(c)) estimated using the model developed by Cahill and Pohl and the measured longitudinal and transverse sound velocities. 13,[28][29][30] Figure 2(d), which shows the variations in temperature of the ZT values, indicates that ZT increases with temperature for all samples.…”
mentioning
confidence: 99%
“…We first reproduced the calculations of Kim et al 11 for the compounds SnSe, 12 In 4 Se 3-x , 13 24 The ZT values (calculated from the extracted transport coefficients) as a function of temperature for the three materials are shown in Fig. 2a; the calculated efficiencies g (T C = 373 K) based on Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…11 For large temperature differences and/or materials with strongly temperature-dependent transport properties, e.g. the binary compounds SnSe 12 and In 4 Se 3-x , 13 Kim et al demonstrated that Eq. 1 can significantly overestimate the energy conversion efficiency in comparison to predictions from finite difference numerical simulations.…”
Section: Introductionmentioning
confidence: 99%